Pengaruh Model Preject Based Learning terhadap Hasil Belajar Peserta Didik tentang Menjaga dan Melestarikan Keragaman Budaya di Kelas V SD Inpres Kuanino 3 Kota Kupang - Ly, Petrus; Kota, Martha Khristina; Darmawati, Salsabillah (Lembaga Yasin AlSys, 2025)
This study aims to examine the significant influence of the use of the Project Based Learning Model on student learning outcomes about maintaining and preserving cultural diversity in grade V of SD Inpres Kuanino 3. This research was carried out at SD Inpres Kuanino 3 Kupang City Classes V A and V B Even Semester of the 2024/2025 Academic Year. This study is quantitative research using a quasi-pretest-posttest control group experimental research design. The experimental class used the Project Based Learning model, while the control class used the conventional Problem Based Learning model. The results of the pretest showed an average score of 47.2 in the experimental class and 34.8 in the control class. After being given treatment, the average posttest score of the experimental class increased to 83.8, while the control class reached 69.8. The normality and homogeneity test showed normal and homogeneous distributed data. The results of the hypothesis test showed that t-count = -21.517 was greater than t-table = 2.064, so it can be concluded that there is a significant influence of the Project Based Learning model on student learning outcomes.